Translating genes into health - Kricka, Larry J; Di Resta, Chiara (Nature genetics, 2013)
A major challenge for genomics is to provide clinical benefits to the genetically diverse human population. Genome science has achieved a catalog of mutations and informative SNPs. Next-generation sequencing is rapidly delivering thousands of complete human genomes, but understanding and applying genomic knowledge remains a daunting undertaking. These challenges and opportunities for genomic medicine were central themes of the Golden Helix Symposium held in Turin, Italy, 18–21 April 2012.